Network Analysis in Relationship Dynamics and Digital Social Identity in Youths - Banepali, Rajendra Man; Shakya, Subarna; Sharma, Gajendra (Journal of the Institute of Engineering, 2018)
People living with digital technology or without technology, no one is immune from digital technology nowadays. Netizen culture became a style of life in youth, the style as new behaviors. Aiming to scrutinize behavior of individual actor of digital network, this study has explored relationship dynamics of digital network observing students in survey. Network theory and cognition theory along with models from various sources have been employed to draw a result from data. Digital social identity and individual network behaviors like pattern of establishing new relation, altering relationship dynamics and termination are result of this work. In future, this model of network analysis can be expanded to various domains like political, intelligence and international relations. Journal of the Institute of Engineering, 2017, 13(1): 225-231